Simulation-Based Comparison of P-Metaheuristics for FJSP with and Without Fuzzy Processing Time - Rim, Zarrouk; Imed, Bennour; Abderrazek, Jemai (Recent Trends and Future Technology in Applied Intelligence, 2018)
The population based metaheuristic (P-metaheuristic) is a stochastic algorithm for optimization. This paper presents five different P-metaheuristics (BAT, Firefly, Cuckoo search, basic Particle swarm optimization (BPSO) and a modified PSO (M-PSO)) for solving Flexible Job Shop Problem with and without fuzzy processing time (FJSP/fFJSP). We intend to evaluate and compare the performance of these different algorithms by using thirteen benchmarks for FJSP and four benchmarks for fFJSP. The results demonstrate the superiority of the M-PSO algorithm over the other techniques to solve both FJSP and fFJSP.